Analisis Kemampuan Berbahasa dan Penanaman Moral pada Anak Usia Dini melalui Metode Mendongeng - Putri Hana Pebriana (LPPM Universitas Pahlawan Tuanku Tambusai, 2017)
A very important factor for the child in expressing his emotions is through language. In addition, moral planting should also be implanted in children from an early age. Language for children can be obtained through experience in everyday life. In this phase, the child experiences a stage of language development that can be said to grow rapidly if the method chosen in the learning process is also appropriate. One method that can be an alternative in developing the language for early childhood is to use the method of storytelling. Indirectly through listening activities children can absorb the information that is on the story. Listening to fairy tales involves adding new vocabulary in story elements as well as moral messages, so by this method the child easily accepts the addition of new vocabulary as well as the moral message contained in a story. Through storytelling it will automatically happen value transformation through the behavior and character of the characters in the story. From the exposure that has been described that the method of storytelling in addition to developing language skills of children, this method can also be used as an alternative in instilling moral in children.